Geochemical Exploration and Processing Studies for Graphite and Tungsten Minerals from Burugubanda-Tapaskonda Areas of East Godavari District - RAMAKRISHNA, CH.; MALLIKARJUNA RAO, D. (Asian Journal of Chemistry, 2010)
Graphite-tungsten mineralization occurs in the graphite schists associated with khondalites from Burugubanda-Tapaskonda areas of East Godavari district. Geochemical and geophysical methods of exploration followed by soil and stream sediment sampling clearly demarcated the zones of tungsten mineralization in association with the graphite ore bodies. The fixed carbon and tungsten contents varies from 6.5-10.5 % Folin-Ciocalteu reagent and 0.1-0.5 % WO3, respectively. The low grade graphite deposits as well as tungsten minerals were subjected to processing studies adopting different techniques to achieve maximum percentage of recovery. The final product of recovery assaying 60-80 % Folin-Ciocalteu reagent and 60-65 % WO3.